A lab-on-a-chip for hypoxic patch clamp measurements combined with optical tweezers and spectroscopy- first investigations of single biological cells - Alrifaiy, Ahmed; Borg, Johan; Lindahl, Olof A; Ramser, Kerstin (Biomedical engineering online, 2015)
The response and the reaction of the brain system to hypoxia is a vital research subject that requires special instrumentation. With this research subject in focus, a new multifunctional lab-on-a-chip (LOC) system with control over the oxygen content for studies on biological cells was developed. The chip was designed to incorporate the patch clamp technique, optical tweezers and absorption spectroscopy. The performance of the LOC was tested by a series of experiments. The oxygen content within the channels of the LOC was monitored by an oxygen sensor and verified by simultaneously studying the oxygenation state of chicken red blood cells (RBCs) with absorption spectra. The chicken RBCs were manipulated optically and steered in three dimensions towards a patch-clamp micropipette in a closed microfluidic channel. The oxygen level within the channels could be changed from a normoxic value of 18% O 2 to an anoxic value of 0.0-0.5% O 2. A time series of 3 experiments were performed, showing that the spectral transfer from the oxygenated to the deoxygenated state occurred after about 227 ± 1 s and a fully developed deoxygenated spectrum was observed after 298 ± 1 s, a mean value of 3 experiments. The tightness of the chamber to oxygen diffusion was verified by stopping the flow into the channel system while continuously recording absorption spectra showing an unchanged deoxygenated state during 5400 ± 2 s. A transfer of the oxygenated absorption spectra was achieved after 426 ± 1 s when exposing the cell to normoxic buffer. This showed the long time viability of the investigated cells. Successful patching and sealing were established on a trapped RBC and the whole-cell access (Ra) and membrane (Rm) resistances were measured to be 5.033 ± 0.412 M Ω and 889.7 ± 1.74 M Ω respectively.